2012
DOI: 10.1890/11-0941.1
|View full text |Cite
|
Sign up to set email alerts
|

Collapse and reorganization of a food web of Mwanza Gulf, Lake Victoria

Abstract: Starchy food products differ in the rate of starch digestion, which can affect their metabolic impact. In this study, we examined how the in vivo starch digestibility is reflected by the glycemic response, because this response is often used to predict starch digestibility. Ten healthy male volunteers [age 21 6 0.5 y, BMI 23 6 0.6 kg/m 2 (mean 6 SEM)] participated in a cross-over study, receiving three different meals: pasta with normal wheat bran (PA) and bread with normal (CB) or purple wheat bran (PBB). Pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 56 publications
1
48
0
Order By: Relevance
“…The once-abundant endemic haplochromine cichlid fauna, which previously accounted for over 80% of the biomass of Lake Victoria (Kudhongania & Cordone, 1974), virtually disappeared from the deepwater and sublittoral regions of Lake Victoria in the mid-to late 1980s, with approximately 40% of the 500+ species in this group believed to have gone globally or locally extinct (Witte et al, 1992;Seehausen et al, 1997b). Many other native species also suffered serious declines during this time period and, as a result, a once diverse and complex assemblage composed of numerous trophic specialists was replaced by a much simpler assemblage dominated by a handful of generalist and omnivorous species (Balirwa et al, 2003;Ojwang et al, 2010;Downing et al, 2012). Similar faunal changes occurred in other lakes in the region where the Nile perch were introduced, including in Lake Kyoga and Lake Nabugabo (Ogutu-Ohwayo, 1993;Chapman et al, 2003).…”
Section: Introductionmentioning
confidence: 83%
“…The once-abundant endemic haplochromine cichlid fauna, which previously accounted for over 80% of the biomass of Lake Victoria (Kudhongania & Cordone, 1974), virtually disappeared from the deepwater and sublittoral regions of Lake Victoria in the mid-to late 1980s, with approximately 40% of the 500+ species in this group believed to have gone globally or locally extinct (Witte et al, 1992;Seehausen et al, 1997b). Many other native species also suffered serious declines during this time period and, as a result, a once diverse and complex assemblage composed of numerous trophic specialists was replaced by a much simpler assemblage dominated by a handful of generalist and omnivorous species (Balirwa et al, 2003;Ojwang et al, 2010;Downing et al, 2012). Similar faunal changes occurred in other lakes in the region where the Nile perch were introduced, including in Lake Kyoga and Lake Nabugabo (Ogutu-Ohwayo, 1993;Chapman et al, 2003).…”
Section: Introductionmentioning
confidence: 83%
“…The diversity collapse and Nile perch boom followed long-term increases in fishing pressure and eutrophication, two processes that had negative impacts on native species [28]. Interestingly, the collapse of haplochromine cichlids in Lake Victoria was accompanied by an increase in the abundance of the shrimp Caridina nilotica , a competitor of the largest cichlid trophic groups [29]. This shrimp became an important food source for Nile perch, but is an unlikely threat to juvenile Nile perch: it could thus represent a case where the insurance effect – seen in shrimp replacing vanishing haplochromines – decreased the resilience of the community to invasion by providing more food for Nile perch but without negatively affecting Nile perch recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the lake has seen a dramatic decrease in the native flora and fauna over the past several decades (Downing et al, 2012;Mkumbo and Marshall, 2014;Witte et al, 2012). Few studies could be found that linked the presence of the water hyacinth to the change in biodiversity (Balirwa et al, 2003;Kateregga and Sterner, 2009).…”
Section: Implications For the Lake Ecologymentioning
confidence: 99%